1981
DOI: 10.2307/1937734
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mites and Nematodes in Early Stages of Buried Litter Decomposition in a Desert

Abstract: We studied changes in populations of mites, nematodes, bacteria, and fungi in buried creosote bush litter treated with selected inhibitors. Elimination of microarthropods (primarily tydeid mites) resulted in increased numbers of bacteriophagic nematodes and reduction in numbers of bacteria; elimination of both nematodes and microarthropods resulted in increased numbers of bacteria compared to untreated controls. Fungal grazing mites, Pyemotidae, and fungivorous nematodes, Aphelenchus sp., increased in numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(54 citation statements)
references
References 17 publications
4
49
0
Order By: Relevance
“…The increased populations of bacterial-feeding nematodes on decomposing plant litter (Fig. 2), have been predominantly Rhabditid nematodes in some studies (Griffiths and Caul, 1993;Griffiths et al, 1994;Wasilewska et al, 1981;Wasilewska and Bienkowski, 1985:), while Cephalobids have predominated in others (Griffiths et al, 1993;Pradhan et al, 1988;Santos et al, 1981;Sohlenius and Bostrom, 1984). The reasons for the preferential development of different groups of bacterial-feeding nematodes is unclear, but maybe related to environmental conditions and the types and abundance of decomposer microorganisms available as food (Bouwman, 1988), and chaotic determination to some extent (Sohlenius, 1993).…”
Section: Effects Of Microfauna On Nutrient Availabilitymentioning
confidence: 91%
“…The increased populations of bacterial-feeding nematodes on decomposing plant litter (Fig. 2), have been predominantly Rhabditid nematodes in some studies (Griffiths and Caul, 1993;Griffiths et al, 1994;Wasilewska et al, 1981;Wasilewska and Bienkowski, 1985:), while Cephalobids have predominated in others (Griffiths et al, 1993;Pradhan et al, 1988;Santos et al, 1981;Sohlenius and Bostrom, 1984). The reasons for the preferential development of different groups of bacterial-feeding nematodes is unclear, but maybe related to environmental conditions and the types and abundance of decomposer microorganisms available as food (Bouwman, 1988), and chaotic determination to some extent (Sohlenius, 1993).…”
Section: Effects Of Microfauna On Nutrient Availabilitymentioning
confidence: 91%
“…Predation on nematodes has also been reported. Santos et al ( 1981 ) studied the relationships between mites identifi ed as Tydeidae (could be Iolinidae) and bateriophagous nematodes in early stages of litter decomposition. They found that the mites affected the nematode numbers and colonization rate in litter decomposition; they showed that elimination of tydeids with the insecticide chlordane resulted in an drastic increase in the population of free living nematodes.…”
Section: Bioecologymentioning
confidence: 99%
“…However, consumers can regulate the assimilation rate of detritus into the food web. Trophic cascades in detritus-based food webs, where predators indirectly affect the rate of organic matter processing, have been reported in soil (Santos et al 1981;Wyman 1998) and stream ecosystems (Oberndorfer et al 1984;Short and Holomuzki 1992;Malmqvist 1993;Konishi et al 2001). Contradictory evidence indicates that trophic cascades may not occur under some conditions (soils: Mikola and Setälä 1998;streams: Reice 1983streams: Reice , 1991Holomuzki and Hatchett 1994;Rosemond et al 1998;Åbjörnsson et al 2000;Usio 2000).…”
Section: Introductionmentioning
confidence: 99%